Conquer & score: a word formation game for language learners / Anealka Aziz and Tuan Sarifah Aini Syed Ahmad - Aziz, Anealka; Syed Ahmad, Tuan Sarifah Aini (Akademi Pengajian Bahasa, 2019)
Engaging students in language activities can sometimes be challenging for language educators. One of the ways to engage students in language activities is through language games. Language games can motivate students to communicate, strengthen their ability to comprehend the language and enhance their problem-solving and cognitive skills. Language games can also increase engagement of the students. This leads to the creation of the Conquer & Score: The Derivational Island. It is a word formation enrichment game catering to students learning lexicology and linguistics. The topic was chosen based on the result of an online quiz on the types of morphemes. The game focuses on the derivational morphemes used to form the English language words. The game requires knowledge of morphology as well as basic lexical analysis skills. The game provides educators a fun and engaging reinforcement activity for the students. Gamification elements used in the game such as rewards, flexible learning path and progress indicator offer a safe environment for competition, which can motivate students to outdo each other to win the game. This paper also highlights some important aspects of games in learning.